2017
DOI: 10.1186/s12958-017-0242-9
|View full text |Cite
|
Sign up to set email alerts
|

5α-reductase activity in women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Background5α-reductase activity might be important during the development of polycystic ovary syndrome (PCOS). However, the changes of 5α-reductase activity in PCOS subjects and the relationship between 5α-reductase activity and body mass index (BMI), insulin resistance (IR) remain largely unknown.MethodsWe performed a meta-analysis to examine 5α-reductase activity in women with PCOS; exploratory subgroup analyses were also performed.ResultsFive articles (with 356 cases and 236 controls) reporting 5α-reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…AUC glucose (Area under the curve of blood glucose) = 1/4 × FBG + 1/2 × PBG30′ + 3/4 × PBG60′ + PBG120′ 20 . The insulin resistance index is defined as the ratio of HOMA-IR (Homeostasis model assessment) 21 .…”
Section: Methodsmentioning
confidence: 99%
“…AUC glucose (Area under the curve of blood glucose) = 1/4 × FBG + 1/2 × PBG30′ + 3/4 × PBG60′ + PBG120′ 20 . The insulin resistance index is defined as the ratio of HOMA-IR (Homeostasis model assessment) 21 .…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis by Wu et al demonstrates higher proportions of 5α-reductase metabolites in PCOS women compared to BMI matched controls. Moreover, subgroup analyses confirm the association of 5 α reductase with insulin resistance 41 . 5α-reductase indirectly modulates hyperandrogenism; however, the exact mechanism is unclear.…”
Section: Role Of Insulinmentioning
confidence: 73%
“…A study in adult men showed that testosterone reduced the CRH-stimulated rise in serum cortisol, in spite of increased ACTH, suggestive of adrenal hyporesponsiveness (54). Evidence for an effect of androgens on glucocorticoid metabolism was provided by other studies (55,56,57). It has been demonstrated by multiple studies that women with polycystic ovary syndrome -a condition characterized by increased androgen production -had a higher 5α-reductase activity than BMI-matched controls (55).…”
Section: Discussionmentioning
confidence: 99%